2020
DOI: 10.1002/oby.22933
|View full text |Cite
|
Sign up to set email alerts
|

Per‐ and Polyfluoroalkyl Substance Exposure, Gestational Weight Gain, and Postpartum Weight Changes in Project Viva

Abstract: Objective The purpose of this study was to test the extent to which pregnancy per‐ and polyfluoroalkyl substance (PFAS) concentrations were associated with gestational weight gain and postpartum weight changes. Methods This study was composed of 1,614 women recruited between 1999 and 2002 via the Project Viva cohort with pregnancy plasma concentrations of six PFAS, including perfluorooctanesulfonic acid, perfluorooctanoic acid (PFOA), and 2‐(N‐ethyl‐perfluorooctane sulfonamido) acetic acid. Gestational weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Multiple studies reported that certain PFAS measured in maternal blood during pregnancy were associated with greater gestational weight gain [551][552][553][554][555]. Gestational weight gain is associated with greater infant adiposity at birth [556].…”
Section: Human Studiesmentioning
confidence: 99%
“…Multiple studies reported that certain PFAS measured in maternal blood during pregnancy were associated with greater gestational weight gain [551][552][553][554][555]. Gestational weight gain is associated with greater infant adiposity at birth [556].…”
Section: Human Studiesmentioning
confidence: 99%
“…For example, prenatal PFAS exposure has been linked to excessive gestational weight gain ( Ashley-Martin et al. 2016 ; Mitro et al. 2020 ), preterm birth ( Meng et al.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to PFAS has been linked to a wide array of adverse health outcomes, including reproductive outcomes (Blake and Fenton 2020). For example, prenatal PFAS exposure has been linked to excessive gestational weight gain (Ashley-Martin et al 2016;Mitro et al 2020), preterm birth (Meng et al 2018;Waterfield et al 2020), and preeclampsia (Savitz et al 2012;Stein et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, EtFOSAA was linked to prevalent microvascular disease in a non-pregnant U.S. population in the Diabetes Prevention Program Outcomes Study [17]. In prior work in this cohort, we also found that EtFOSAA is associated with higher gestational weight gain [47]. PFAS may be causing increased adiposity by activating PPAR [ 21 22], which is expressed in adipose tissue and regulates adipocyte differentiation as well as fatty acid storage [48].…”
Section: Discussionmentioning
confidence: 61%